STRATEGI KOMUNIKASI PEMASARAN PT. TRIO ELEKTRONIK DALAM MENINGKATKAN PENJUALAN SMARTPHONE MEREK OPPO DI KOTA PEKANBARU - Nanda Alzikri; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Background of this research business based on brand OPPOsmartphone. PT. Trio Elektronik is a company which is located at Jl. Soekarno Hatta, to be precise next to Darma Yudha Pekanbaru school. PT. Trio Elektronik is a company that holds only onebrand smartphone OPPOin the Pekanbaru city area. The excellence of the Oppo smartphone lies in the camera with large megapixels so that it can produce good photos. Likewise, the large RAM can store more applications at a low price compared to smartphones other. As for the problem in this study how the marketing communication strategy carried out by PT. Trio Elektronik in increasing sales smartphones of OPPO brandin Pekanbaru City. The purpose of this study is to determine the form of advertising carried out by PT. Trio Elektronik in increasing sales smartphones of OPPO brandin Pekanbaru City, to find out the form of event marketing conducted by PT. Trio Elektronk in increasing sales smartphones of OPPO brandin Pekanbaru City, to determine the form of individual sales carried out by PT. Trio Elektronk, in increasing sales smartphones of OPPO brandin Pekanbaru City, to find out the form of direct sales made by PT. Trio Elektronk in increasing sales smartphones of OPPO brandin Pekanbaru City and to find out about the form of segmentation targeting positioning (STP) carried out by PT. Trio Elektronk in increasing sales of OPPO brand smartphones in Pekanbaru City. The method used in research using qualitative methods with a descriptive approach, this is an attempt to describe events based on existing facts and evidence. The qualitative approach is expected to be able to produce an in-depth description of speech, writing, and behavior that can be observed from certain individuals, groups, communities and organizations in a particular context setting that is studied from a complete perspective. As for the results of this research in this case advertising is quite effective in conveying an information, Sales made by PT. Trio Elektronik Kota Pekanbaru can be said to be effective because this activity uses marketing personnel or what is commonly said to be a salesman who interacts directly with consumers to offer and explain product specifications and prices for consumer purposes. Event Marketing, Targeting Positioning Strategy, individual sales activities are only to support other promotional programs. Keyword: Strategy, Communication Strategy of Marketing , Smartphone Oppo